PENATALAKSANAAN FISIOTERAPI PADA ANAK CEREBRAL PALSY DENGAN KONDISI CONGENITAL TALIPES EQUINO VARUS MENGGUNAKAN METODE NEURO DEVELOPMENT TREATMENT - Lazimah .; Nur Susanti (LPPM Universitas Pekalongan, 2013)
Congenital talipes equino varus or usually called by club foot is deformity that commonly occured in children. The factor which affect occuring CTEV at cerebral palsy is disturbance for intrauterine mechanical which caused aberration of fetus development during pregnancy. Problems regarding condition of Cerebral palsy with CTEV is limited of base of support so the kid will obtain disturbance in functional ability specially for self balancing in standing and walking. Because this matter also supported by postural control required skin touch of foot. Intervention including all of phisiotherapy measurement that is an examination for spasticity by Asworth Scale, an examination for identifying in serious condition of CTEV by the pirani scoring system and an examination for functional ability by Gross Motor Functional Measurement (GMFM). In this case to contend the problems above may used modality sort of Neuro Development Treatment. From the result obtained. It can concluded that use of NDT can help reduce the problems that arise in this case.Key words : Congenital Talipes Equino Varus, Cerebral Palsy and Neuro Development Treatment.